PINK1 primes parkin-mediated ubiquitination of PARIS in dopaminergic neuronal survival - Lee, Yunjong (Cell Rep, 2017)
Mutations in PTEN-induced putative kinase 1 (PINK1) and parkin cause autosomal-recessive Parkinson’s disease through a common pathway involving mitochondrial quality control. Parkin inactivation leads to accumulation of the parkin interacting substrate (PARIS, ZNF746) that plays an important role in dopamine cell loss through repression of proliferator-activated receptor gamma coactivator-1α (PGC-1α) promoter activity. Here we show that PARIS, links PINK1 and parkin in a common pathway that regulates dopaminergic neuron survival. PINK1 interacts with and phosphorylates serines 322 and 613 of PARIS to control its ubiquitination and clearance by parkin. PINK1 phosphorylation of PARIS alleviates PARIS toxicity as well as repression of PGC-1α promoter activity. Conditional knockdown of PINK1 in adult mouse brains leads to a progressive loss of dopaminergic neurons in the substantia nigra that is dependent on PARIS. Together, these results uncover a function of PINK1 to direct parkin-PARIS regulated PGC-1α expression and dopaminergic neuronal survival.